The Impact of Fiscal and Monetary Policies on Indonesia’s Economic Performance: A Critical Analysis - Wulansari, Suci Diana; Rachmaniyah, Bunga Ayufi; Reswara, Krisna; Oktavia, Renny (Journal of Regional Economics Indonesia, 2024)
Fiscal and monetary policies are crucial in steering the direction of a nation’s economy, necessitating coordination to achieve targeted economic growth. This paper explores the character and real-world implementation of fiscal and monetary policies and their implications for Indonesia’s economic direction and performance, based on a literature review. Fiscal policy, primarily shaped by taxation policy, aims to: (i) stimulate economic growth, (ii) promote income distribution equity, and (iii) finance government expenditures. These objectives align with key fiscal priorities, namely: (i) economic recovery, (ii) economic transformation, and (iii) social equity. Meanwhile, monetary policy supports accelerated economic recovery through (i) expansionary and (ii) consolidation policies. Effective monetary policy coordination with fiscal policy is essential to achieve broader macroeconomic goals, highlighting the need for cohesive policy alignment to foster sustainable development.